Modeling and mapping QTL for senescence-related traits in winter wheat under high temperature - Vijayalakshmi, Kolluru; Fritz, Allan K; Paulsen, Gary M; Bai, Guihua; Pandravada, Satchidanand; Gill, Bikram S (Molecular breeding, 2010)
Senescence is a genetically programmed and environmentally influenced process resulting in the destruction of chlorophyll and remobilization of nutrients to younger or reproductive parts of plants. Delayed senescence, or stay-green, contributes to a long grain-filling period and stable yield under stress. To model senescence and identify quantitative trait loci (QTL) for the trait, a population of recombinant inbred lines (RIL) from a cross between winter wheat cultivars, ‘Ventnor' and ‘Karl 92' was evaluated for heat tolerance under optimum temperature of 20/15°C (day/night) and continuous heat stress of 30/25°C from 10 days after anthesis (DAA) until maturity. Ventnor is a heat-tolerant cultivar and Karl 92 is a relatively heat-susceptible cultivar. Green leaf area was measured and used to model percent greenness retained over the reproductive period. Chlorophyll content and chlorophyll fluorescence were recorded on flag leaves. Senescence was converted to a quantitative trait using the model. Based on the modeled parameters, the RILs were categorized into three groups. When senescence-related traits were evaluated, nine QTL for heat tolerance were found on chromosome 2A, two each on chromosomes 6A and 6B and one each on chromosome 3A, 3B, and 7A. Both parents contributed favorable alleles for most of the senescence-related traits. Microsatellite markers Xgwm356 and Xgwm5 prominently linked to the senescence-related traits may be useful in marker-assisted breeding. These and the linked AFLP (amplified fragment length polymorphism) markers XCGT.TGCG-349, XCGT.GTG-343, and XCGT.CTCG-406, if converted to STS (sequence tagged sites), can be used for further molecular dissection of the QTL for post-anthesis heat tolerance.